2014
DOI: 10.1080/00313831.2014.904426
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Reasoning, School Achievement and Gender: a Multilevel Study of between and within School Effects in Finland

Abstract: The relationships between reasoning and school achievement were studied taking into account the multilevel nature (school-and class-levels) of the data. We gathered data from 51 classes at seven schools in metropolitan and Eastern Finland (N = 769, 395 males, 15-year-old students). To study scientific reasoning, we used a modified version of Science Reasoning Tasks, tapping control-of-variable schemata. Analyses were conducted by MLwiN2.10 multilevel modelling. The present results showed that the intra-class c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
1
8
0
2
Order By: Relevance
“…The effects found in the present study suggest something about student assignment practices. This agrees with the previous literature, the non-random sorting of students into classrooms is one way to manage student diversity in schools, especially concerning students with SEN, yet, the purposeful sorting of students is not a neutral act and can increase further the between-class differences discovered to be relatively high in Finnish schools (Thuneberg et al, 2015;Yang Hansen et al, 2014).The differences between classes may often result more from classroom assignment practices than from actual compositional effects. Although Finnish basic education is provided within a single structure without clear division into primary (grades 1-6) and lower secondary (grades 7-9) education, in many municipalities there still are separate schools for them.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The effects found in the present study suggest something about student assignment practices. This agrees with the previous literature, the non-random sorting of students into classrooms is one way to manage student diversity in schools, especially concerning students with SEN, yet, the purposeful sorting of students is not a neutral act and can increase further the between-class differences discovered to be relatively high in Finnish schools (Thuneberg et al, 2015;Yang Hansen et al, 2014).The differences between classes may often result more from classroom assignment practices than from actual compositional effects. Although Finnish basic education is provided within a single structure without clear division into primary (grades 1-6) and lower secondary (grades 7-9) education, in many municipalities there still are separate schools for them.…”
Section: Discussionsupporting
confidence: 89%
“…In Finland, the differences between classes is relatively high, accounting on average for 10 to 15 percent of the variation in different test achievement (Thuneberg, Hautamäki, & Hotulainen, 2015;Yang Hansen, Gustafsson, & Rosén, 2014). In many school-effect studies, achievement differences are found to be related to differences in the composition of the student body (Harker & Tymms, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to Thuneberg et al (2015), girls in Organization for Economic Cooperation and Development (OECD) countries almost always have higher marks in GPA and PISA than boys. This conclusion is also supported by the study findings that the GPAs of females were significantly greater than that those of males.…”
Section: Discussionmentioning
confidence: 99%
“…A Piagetian formal operations tasks was used to assess level of formal thinking (Hautamäki, 1989;Thuneberg et al, 2015). For instance, participants were asked to consider F1 drivers, cars, tires, and race tracks (four variables each, all with two given values from which to select: Räikkönen, Schumacher; Ferrari, McLaren; Michelin, Bridgestone; Monaco, Silverstone).…”
Section: Scientific Reasoningmentioning
confidence: 99%